Assessment and correction of the risk of cardiac complications during non-cardiac surgery - A. N. Sumin (Рациональная фармакотерапия в кардиологии)
About 300 million non-cardiac operations are performed annually worldwide. In developed countries, an increasing number of such operations are performed in older patients with comorbid cardiac pathology. The leading cause of perioperative mortality is cardiovascular complications. The national and international guidelines published in the last year on cardiovascular assessment and correction of the risk of cardiac complications during non-cardiac operations contain several contradictory provisions. First of all, this refers to the methods of preoperative risk assessment: which is better — to base on scales, functional status assessment or biomarkers (BNP/ NT-pro-BNP) determination? Questions remain about the most appropriate algorithm for preoperative evaluation of patients with suspected cardiac pathology (the need for preoperative non-invasive tests or limited to biomarkers evaluation), some of these algorithms have been validated in recent studies. Several publications address the problem of drug therapy in non-cardiac surgery, both previously studied drugs (statins, beta-blockers) and new ones (colchicine, nicorandil). Perioperative myocardial injury syndrome and its possible drug prevention continue to be studied. This review considers recent publications on this topic, which have not yet been reflected in the guidelines and may influence their correction in the future. The article also discusses the problems of implementing existing guidelines in clinical practice. The publications of the last year presented in the review help researchers and practitioners to form their views on existing controversial issues. Ultimately, this will promote the use of an individualized approach in the management of this category of patients.